Expanding Women's Access to Land and Housing in Urban Areas - Rakodi, Carole (World Bank, Washington, DC, 2014)
Evidence is mounting that secure property rights have positive effects for poor people in general and women in particular. The aim of this report is to review what is known about women s access to and control over land and real property in urban settings, identifying approaches to strengthening property rights that enhance women s agency, and sharing key lessons. Section two synthesizes the evidence on urban women s priorities with respect to land and housing; the factors that influence women s access to and control over land and secure tenure, including legal and institutional frameworks and social relationships, especially within the family; and what is known about the extent to which women have access to, control over and use of urban land and housing, and through what forms of tenure. In section three, recent reform of laws, policies and practices to meet the needs of poor people in urban areas, especially women, will be assessed. Section four provides a short discussion of some of the strategies, tactics and alliances that are being adopted to bring about legal reforms and to influence the content, design and implementation of programs in urban areas. The report draws on successive research projects by the author and her colleagues on land and housing markets and policies, urban livelihoods, and urban politics and governance in a variety of contexts, in particular Rakodi (2010).